A smart experimental setup for vibration measurement and imbalance fault detection in rotating machinery. (December 2016) - Yamamoto, Guilherme Kenji; da Costa, Cesar; da Silva Sousa, João Sinohara
Abstract: Rotor imbalance is the most common cause of machine vibration. In practice, rotors can never be balanced perfectly owing to manufacturing errors such as porosity in casting, non-uniform density of materials, manufacturing tolerances, and gain or loss of material during operation. Mass imbalance leads to the generation of a centrifugal force, which must be counteracted by bearings and support structures. A full spectrum analysis is presented for vibration signal to reveal the fault specific whirl signatures. The results clearly indicate the potential and feasibility of the discussed approach for the rotor imbalance diagnosis in a rotor shaft system coupled with a three phase induction motor. This paper presents a smart experimental method for vibration measurement and imbalance fault detection in rotating machinery.